A new species of the ant-parasitizing genus Pseudacteon Coquillett (Diptera, Phoridae) from China - Zhang, Jiao; Liu, Guang-Chun (Zootaxa, 2019)
A new scuttle fly of the genus Pseudacteon Coquillett, P. trapeziformis, from Mt. Changbai, northeat China is described and illustrated. The new species is distinguished from others of the genus mainly by shorter palp bristles and trapezoid sternite VI. A key to known Pseudacteon species of China is presented.